INTERNATIONAL EXPERIENCES IN THE ACTIVITIES OF SELF-REGULATORY ORGANIZATIONS IN IMPROVING THE QUALITY OF HOUSEHOLD SERVICES AND THE USE OF THESE EXPERIENCES - B. A. Yerejepova (Modern American Journals, 2025)
The article examines the institutional role of self-regulatory organizations (SRO) in service quality management and their effectiveness in various countries. SROs improve quality through standards, monitoring, and enforcement in service sectors such as advertising, financial intermediation, legal aid, professional services, and construction. Conclusions are provided based on materials from OECD, FINRA (USA), ASA (Great Britain), JSDA (Japan), Canadian legal societies and Korean advertising, as well as documents on SROs in Uzbekistan and local studies.
Keywords: Household services, efficiency, service quality, self-regulating organization, model, standardization, monitoring.